The methods of the modern poets of Iraq and their poetic images 19751945 (Journal of the College of Basic Education, 2023)
Each time phase has its origins and variables whose effects and effects are reflected on the overall activity.Intellectual, cultural and political, and since man is the builder of the environment, interaction and cross-pollination must occur between them.Which leads to the outbreak of conflict at times, and attraction at other times. If this seems familiar to a person, then it isIt seems bright and clear to the human writer and poet, because of the abilities and capabilities of the latter.and qualifications and an important role in building life and society and what it constitutes of cohesion and close connection with the environment and the surroundingsWho lives in the midst of it, life, time and the environment cast a shadow over the poet's spirit and his concerns.The poet derives from it copies of life, as the poet is close to his life and his tools from it, and this has become an obvious mistake.It is an inevitable trend in which he lives and lives according to special standards that differ from one place to another, and from one place to another.environment and time to time. This intimate connection motivates the poet to be distinguished, rather he must be distinguished, and this isDistinction is an indication of it, which prompts him to search for a specific language and a special style that distinguishes him from the others.And the poets who preceded them again. This calligraphy and style is known, famous, and studied.Therefore, language should be the basis of poetry, and poetic methods and images should be the essence of creativity.The march attracted the attention of researchers, scholars and critics.